1982
DOI: 10.1161/01.cir.65.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial conduction: a major determinant of R-wave amplitude during acute myocardial ischemia.

Abstract: SUMMARY The relationship of changes in ventricular activation patterns and variations in R-wave amplitude on the surface ECG during the hyperacute phase of myocardial ischemia were studied in nine open-chest dogs. The sum of R-wave amplitude (2RWA) changes in surface ECG leads L2, V5 and Frank orthogonal leads X, Y and Z were correlated with changes in the conduction time along the specialized conduction.system and in intramyocardial conduction times, as well as with hemodynamic and echocardiographically deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 34 publications
1
34
0
1
Order By: Relevance
“…The mechanisms of the terminal QRS distortion are explained by a prolongation of the electrical conduction in the Purkinje fibers in the ischemic region. 10,11) The delayed conduction decreases the degree of cancellation, resulting in an increase in R wave and decrease in the S-wave amplitude in leads with terminal S waves on the surface ECG. [12][13][14] The Purkinje fibers are less sensitive to ischemia than the contracting myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the terminal QRS distortion are explained by a prolongation of the electrical conduction in the Purkinje fibers in the ischemic region. 10,11) The delayed conduction decreases the degree of cancellation, resulting in an increase in R wave and decrease in the S-wave amplitude in leads with terminal S waves on the surface ECG. [12][13][14] The Purkinje fibers are less sensitive to ischemia than the contracting myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similar findings were observed in other experimental studies. [2][3][4][5] These reports have demonstrated that extracellular K + at the ischemic area is increased in association with decreased conduction velocity. It is postulated that Circulation Journal Vol.69, June 2005 this regional hyperkalemia delays conduction velocity.…”
mentioning
confidence: 97%
“…This decreased conduction velocity during myocardial ischemia is manifested as QRS prolongation in the surface ECG. [1][2][3][4][5] Holland and Brooks produced ischemia in the anterior wall of the myocardium after acute ligation of the left anterior descending coronary artery in pigs and demonstrated QRS prolongation. 1 Similar findings were observed in other experimental studies.…”
mentioning
confidence: 99%
“…Previous studies in experimental animals have shown that acute myocardial ischemia results in a decreased conduction velocity of the myocardium, which manifests as QRS prolongation on the surface electrocardiograph (ECG). [3][4][5][6][7] Prolonged QRS duration on the standard 12-lead ECG during exercise has been demonstrated in CAD patients, [8][9][10][11][12] but it is difficult to detect subtle changes in the prolongation of the QRS interval on the standard 12-lead ECG. However, these can be evaluated by using the filtered QRS wave duration (fQRSd) on the signal-averaged ECG (SAECG).…”
mentioning
confidence: 99%